Hematite-Gamma Alumina-based Solid Catalyst Development for Biodiesel Production from Palm Oil - Rizkiana, Jenny; Bryan, Bryan; Gozali, Edbert; Bustomi, Agus Tendi Ahmad; Prakoso, Tirto (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
This research investigated the performance of hematite-gamma alumina (Fe2O3/γ-Al2O3) catalyst in biodiesel production from palm oil. A full factorial experimental design was utilized to analyze the effect of hematite content, catalyst loading, and methanol-to-oil ratio on catalyst performance. From the experiment, biodiesel in the range of 73.6 to 87.6% FAME content was obtained. It was concluded that the catalyst composition, the methanol-to-oil ratio, and the catalyst loading have a significant effect on the FAME content of the biodiesel. Hematite has strong affinity for fatty acids, so a larger hematite surface area will result in a higher fatty acid absorption capacity. The addition of excess methanol can reduce the contact inhibition between the reactants and the active site of the catalyst, thereby increasing the conversion rate of the reaction. Moreover, a higher amount of catalyst loading can result in an increase in the FAME content when accompanied by an increase in the hematite content of the catalyst.